Attention Drives Emotion: Voluntary Visual Attention Increases Perceived Emotional Intensity. (June 2019) - Mrkva, Kellen; Westfall, Jacob; Van Boven, Leaf
Attention and emotion are fundamental psychological systems. It is well established that emotion intensifies attention. Three experiments reported here ( N = 235) demonstrated the reversed causal direction: Voluntary visual attention intensifies perceived emotion. In Experiment 1, participants repeatedly directed attention toward a target object during sequential search. Participants subsequently perceived their emotional reactions to target objects as more intense than their reactions to control objects. Experiments 2 and 3 used a spatial-cuing procedure to manipulate voluntary visual attention. Spatially cued attention increased perceived emotional intensity. Participants perceived spatially cued objects as more emotionally intense than noncued objects even when participants were asked to mentally rehearse the name of noncued objects. This suggests that the intensifying effect of attention is independent of more extensive mental rehearsal. Across experiments, attended objects were perceived as more visually distinctive, which statistically mediated the effects of attention on emotional intensity.